Relational Processes in Ayahuasca Groups of Palestinians and Israelis - Roseman, Leor; Ron, Yiftach; Saca, Antwan; Ginsberg, Natalie; Luan, Lisa; Karkabi, Nadeem; Doblin, Rick; Carhart-Harris, Robin (Frontiers in Pharmacology, 2021)
The abstract is not currently available, please wait for the final typeset article to be published